2016
DOI: 10.1007/s10898-016-0407-7
|View full text |Cite
|
Sign up to set email alerts
|

SOP: parallel surrogate global optimization with Pareto center selection for computationally expensive single objective problems

Abstract: This paper presents a parallel surrogate-based global optimization method for computationally expensive objective functions that is more effective for larger numbers of processors. To reach this goal, we integrated concepts from multi-objective optimization and tabu search into, single objective, surrogate optimization. Our proposed derivative-free algorithm, called SOP, uses non-dominated sorting of points for which the expensive function has been previously evaluated. The two objectives are the expensive fun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 27 publications
0
28
0
Order By: Relevance
“…The proposed SOP algorithm showed good speed up with up to 64 processors per iteration. In previous studies before their SOP study (Krityakierne et al 2016), the maximum number of processors in parallel with global surrogate optimization was not larger than 10. Given P processors, SOP selects P evaluation points for the next iteration from candidate points generated around P center points.…”
Section: Literature Reviewmentioning
confidence: 98%
See 4 more Smart Citations
“…The proposed SOP algorithm showed good speed up with up to 64 processors per iteration. In previous studies before their SOP study (Krityakierne et al 2016), the maximum number of processors in parallel with global surrogate optimization was not larger than 10. Given P processors, SOP selects P evaluation points for the next iteration from candidate points generated around P center points.…”
Section: Literature Reviewmentioning
confidence: 98%
“…The value of the weight between the surrogate estimation and distance criteria is varied to select as many evaluation points as there are processors. Krityakierne et al (2016) proposed the SOP algorithm for parallel computation and reported that there are a few studies on parallel surrogate global optimization that scaled up to many processors. The proposed SOP algorithm showed good speed up with up to 64 processors per iteration.…”
Section: Literature Reviewmentioning
confidence: 99%
See 3 more Smart Citations